Group of All Taxicab Isometries: A Combinatorial Approach - Neswan, Oki; Sumartono, Harry (Department of Mathematics, Universitas Negeri Gorontalo, 2024)
In this work, we give a more thorough and exhaustive proof of the set of all isometries in taxicab geometry using a combinatorial approach. We show that isometries preserving taxicab distance while leaving the origin fixed are uniquely determined by how they permute the vertices of circles. Then, we use this principle to identify all isometries in taxicab geometry.